Evolution of Microstructure during Rapid Solidification of SiC under High Pressure. (23rd February 2022) - Yan, Wanjun; Qin, Xinmao; Zhang, Zhongzheng; Zhang, Chunhong; Gao, Tinghong
Abstract : The microstructure evolution of liquid silicon carbide (SiC) during rapid solidification under different pressure values is simulated with the Tersoff potential using molecular dynamics. The structure evolution characteristics of SiC are analyzed by considering the pair distribution function, bond angle distribution, coordination number, and the diagrams of the microstructure during rapid solidification. The results show that the average energy of atoms gradually increases with pressure. When the pressure reaches 100 GPa, the average energy of the atom is greater than the average energy of the atom in the initial liquid state. Under different pressures, the diffusion of atoms tends to remain stable at a temperature of about 3700 K. The application of pressure has a major impact on the arrangement of atoms, except on the third-nearest neighbor, while the impact on the nearest neighbor and the second-nearest neighbor is relatively small. The pressure increases the medium-range order of the system. The coordination numbers of Si and C atoms gradually decrease with the decrease in temperature and increase in pressure. Pressure changes the microstructure of the SiC amorphous system after solidification, and the density can be increased by adjusting the coordination number of atoms. As the pressure increases, the SiC amorphous system exhibits a dense structure with coordination numbers of 4, 5, 6, and 7.